Organizational Commitment Versus Career Commitment - Herachwati, N; Rachma, A (KnE Social Sciences, 2018)
This study aims to determine the effect of career satisfaction on organizational commitment and career commitment. In addition, the study also aims to determine the effect of organizational commitment as variables that mediate the relationship between career satisfaction and career commitment. The sample used in this study is comprised of employees at a manufacture and service company. The data analysis in this study is conducted using the Partial Least Square (PLS). The results prove the existence of significant effects related to these following hypotheses: the influence of career satisfaction on career commitment; the influence of career satisfaction on organizational commitment; the influence of organizational commitment on career commitment; the influence of career satisfaction on career commitment through organizational commitment. Keywords: career satisfaction, organizational commitment, career commitment